Early Warning Alone Is Not Enough: Rethinking Disaster Preparedness Through Resource Mobilization - Sunarto Sunarto; Suparji Suparji; Heru Santoso Wahito Nugroho; Gusman Arsyad; Nina Indriyawati (Knowledge Dynamics, 2025)
The effectiveness of disaster preparedness cannot be measured solely from the existence of an early warning system (EWS). Warnings without prompt and coordinated action risk losing their significance in saving lives. In practice, many regions face challenges when warning signals are received, but response and resource mobilization are slow. This demonstrates that preparedness does not stop at detection systems, but rather relies on institutional, social, and technical capacity to act promptly. This opinion piece examines the limitations of EWS implementation in Indonesia from three dimensions: technical (limited reach and data interoperability), social (low risk literacy and community engagement), and institutional (unintegrated command, logistics, and anticipatory financing). This condition is exacerbated by weak coordination at the local level, including in the activation of volunteers and social networks, so that vulnerable groups are often not reached by warnings or early assistance. Based on lessons learned from case studies in Indonesia and international literature on anticipatory action, this paper emphasizes the need to review preparedness indicators by including aspects of resource mobilization as a main component. Policy recommendations include strengthening the capacity of Disaster Resilient Villages in the dissemination of warnings (last-mile warning), the application of the mechanism trigger and anticipatory financing, as well as the integration of preparedness with health services, education, logistics, search and rescue, and refugee readiness. This new approach positions preparedness not simply as the ability to receive warnings, but as an integrated system capable of translating warnings into concrete, life-saving actions.